Incidence of hoof and leg injuries in dairy cow under different floor - UPADHYAY, DEEPAK; SINGH, MUKESH; GAUR, GYANEDRA KUMAR; VERMA, MED RAM (The Indian Journal of Animal Sciences, 2023)
Present study explored the effect of different floor on hoof health and leg injuries of crossbred dairy cow. Animals (n=24), were randomly assigned into four groups with different floor combination in covered and open area, viz. T0 (concrete and brick paved), T1 (concrete and sand), T2 (rubber mat and sand) and T3 (rubber mat and brick paved). Hoof and limb lesion scores were recorded as per the standard protocol during study period. White line lesion score did not differ significantly, however, sole lesion score and inter-digital space lesion score differed significantly between the groups. Both, sole and interdigital space lesion scores were greater in T0 group. Total hoof lesion score was different between the groups with highest value in T0 group. Month wise hoof lesion scores differed significantly in 5th and 6th month between treatments. Decreasing trend was noticed in T1 and T2 from 5th month onwards. In contrast, T0 showed increase in hoof lesion score. Knee lesion score and hock lesion score were different between treatments. Higher scores were found in cows housed in T0 group, while lower scores were noted in T1 group. Knee lesion score decreased in T1 and T2 groups 4th month onwards, however no change was seen in T0 and T3 group. Similar trend was also seen for hock lesion score. In conclusion, provision of sand bed floor in open area of loose house with or without rubber mat floor in covered area was found superior for improving animal welfare in terms of lesser hoof and limb injuries.